The multifaceted relationship between accounting, innovative entrepreneurship, and knowledge management : theoretical concerns and empirical insights - Spanò, Rosanna; Di Paola, Nadia (Emerald points., 2019)
The interplay between accounting, innovative entrepreneurship, and knowledge management is an increasingly crucial and yet under-researched topic. These apparently compartmental debates need to be integrated and comprehended as a whole to support the entrepreneurial adventure in this new era.This book proposes a novel approach to the understanding of an entrepreneurial world that is quickly changing. It ties together the debates surrounding control, innovative entrepreneurship, and knowledge management, and acknowledges that there is a need to build a bridge between theory and practice. In doing so it provides a rich empirical analysis to support and complement the theoretical issues raised. The book offers a profound but easily understandable theoretical systematization, to date unavailable, alongside relevant practical and policy implications drawn from real case studies and business plans.The book will prove a useful and thought-provoking read to academic researchers and practitioners who are interested in the key interplay of these previously isolated disciplines.